The influence of audio communications technology on computer-supported collaborative learning - Denise Whitelock; Eileen Scanlon; Josie Taylor (Association for Learning Technology, 1996)
In recent years there has been an appreciation of the benefits that can be obtained by students working in groups or teams using computers (Eraut and Hoyles, 1988). But there is a difference in opinion as to how a partner enhances learning, and in particular how well adult learners do in the collaborative setting. In order to capitalize on the opportunities offered by new technologies, we need to understand more fully how the process of collaboration is effected by different communication technologies, and how the technologies themselves might be used to best advantage for the benefit of distance learners. However, another factor, apart from the technology itself, which is thought to influence computer-supported collaborative learning is in the gender distribution of the group. A number of classroom studies have shown gender differences when children work together with computers, and these have been reported from a number of subject-domains including science (Scanlon et al, 1993; Littleton et al, 1992). Since our own expertise is in the area of science learning, we selected a non-trivial physics task for the subjects to work with, and that is in the area of elastic collisions. Previous studies (Villani and Pacca, 1990; Whitelock et al, 1993) have shown that both adults and school-children have difficulty in predicting the subsequent motion of balls or ice pucks after they collide. Villani's study stresses that even postgraduate students tend to revert to their informal commonsense notions unless they are cued to use formal representations of these types of problem. These studies have demonstrated that the topic of elastic collisions is a complex yet fruitful one in which to engage students in group work.